1996
DOI: 10.1111/j.1468-3148.1996.tb00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour Problems Among Children with Down's Syndrome: Prevalence, Persistence and Parental Appraisal

Abstract: Changes over time in the pattern of behaviour problems shown by 91 children with Down's syndrome, together with maternal appraisal of the seriousness of reported problems, were investigated through questionnaires completed by mothers. Fiftyfour individual behaviours were studied at mean ages 9 years 2 months and 13 years 9 months. There was a significant decline in the overall frequency of behaviour problems and in some disturbed behaviours, sleeping and toileting problems, and over-activity. Only one problem-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
(12 reference statements)
1
13
0
Order By: Relevance
“…These factors might contribute to the higher psychopathology in the mothers of autistic children than in those of mentally retarded children in our study. Developmental stage was also reported to affect parental stress (32). Of note, speech development were better in children with autism in our study than those with mental retardation (60% speech positive in autism group vs 40% in mental retardation group).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…These factors might contribute to the higher psychopathology in the mothers of autistic children than in those of mentally retarded children in our study. Developmental stage was also reported to affect parental stress (32). Of note, speech development were better in children with autism in our study than those with mental retardation (60% speech positive in autism group vs 40% in mental retardation group).…”
Section: Discussionmentioning
confidence: 44%
“…Although there were no difference in autism group, mothers of younger children (<3 yr of age) had lower depression, state and trait anxiety scores than those of older children (3 to 6 yr and >6 yr of age) in mental retardation group. Turner and Sloper (1996) reported that there were a significant decline with age in the frequency of behaviour problems and disturbed problems in children with Down's syndrome, but many problems were found to be persistent (32). The few number of young children in autism and mental retardation group made it difficult to draw accurate conclusions regarding the age of the children, but we can conclude that mothers of autistic children had increased psychopathology from the early ages of their children while mothers of mentally retarded children had increased psychopathology at slighty later ages of their children (>3 yr of age).…”
Section: Discussionmentioning
confidence: 99%
“…0.59 over 5 years, Kiernan & Alborz 1996; 0.40 over 12 years, Murphy et al . 2005; 0.86 over about 4 years, Turner & Sloper 1996). All of this information indicates that challenging behaviour is not a transient phenomenon, but persistent over very long periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…Persistence percentages refer to the percentage of people identified as showing severe challenging behaviour at Time 2 among those who were identified with severe challenging behaviour at Time 1, an index used in other longitudinal studies (e.g. Turner & Sloper 1996; Emerson et al. 2001b).…”
Section: Introductionmentioning
confidence: 99%
“…The Additional Behavioural Inventory (ABI) designed in the earlier study was used for global assessment of behavioural problems. The 26 items of the ABI were clustered in five groups (Turner & Sloper 1996). These five groups of behaviour profiles were: Conduct disorder, Habit/rituals, Disturbed behaviour, Person related and Activity.…”
Section: Methodsmentioning
confidence: 99%